Copper(II)–Thymine Coordination Polymer Nanoribbons as Potential Oligonucleotide Nanocarriers. (9th December 2016) - Vegas, Verónica G.; Lorca, Romina; Latorre, Ana; Hassanein, Khaled; Gómez‐García, Carlos J.; Castillo, Oscar; Somoza, Álvaro; Zamora, Félix; Amo‐Ochoa, Pilar
Abstract: The direct reaction between copper nitrate, thymine‐1‐acetic acid, and 4, 4′‐bipyridine in water leads to the formation of a blue colloid comprising uniform crystalline nanoribbons (length >1 μm; width ca. 150–185 nm; diameter ca. 15–60 nm) of a coordination polymer. The polymer displays a thymine‐based structure freely available for supramolecular interactions. These nanostructures show significant selective interaction with single‐stranded oligonucleotides based on adenine. Remarkably, they present low cell toxicity in three cell lines–despite the copper(II) content–and can be used as nanocarriers of oligonucleotides. These results suggest the potential of these types of nanostructures in several biological applications.